Application layer HTTP-GET flood DDoS attacks: Research landscape and challenges. Issue 65 (March 2017) - Singh, Karanpreet; Singh, Paramvir; Kumar, Krishan
Abstract: Application layer Distributed Denial of Service (DDoS) attacks have empowered conventional flooding based DDoS with more subtle attacking methods that pose an ever-increasing challenge to the availability of Internet based web services. These attacks hold the potential to cause similar damaging effects as their lower layer counterparts using relatively fewer attacking assets. Being the dominant part of the Internet, HTTP is the prime target of GET flooding attacks, a common practice followed among various application layer DDoS attacks. With the presence of new and improved attack programs, identifying these attacks always seems convoluted. A swift rise in the frequency of these attacks has led to a favorable shift in interest among researchers. Over the recent years, a significant research contribution has been dedicated toward devising new techniques for countering HTTP-GET flood DDoS attacks. In this paper, we conduct a survey of such research contributions following a well-defined systematic process. A total of 63 primary studies published before August 2015 were selected from six different electronic databases following a careful scrutinizing process. We formulated four research questions that capture various aspects of the identified primary studies. These aspects include detection attributes, datasets, software tools, attack strategies, and underlying modeling methods. The field background required to understand the evolution of HTTP-GET flood DDoS attacks is also presented. The aim of this systematic survey is to gain insights into the current research on the detection of these attacks by comprehensively analyzing the selected primary studies to answer a predefined set of research questions. This survey also discusses various challenges that need to be addressed, and acquaints readers with recommendations for possible future research directions.